A 60 year old female with redness of eye turns to periorbital swelling with nasal bleeding - Akter , Sharmin (Bangladesh Journal of Medicine, 2024)
Mrs. X, 60 year old hypertensive , diabetic, known case of CKD, non-asthmatic patient came to PMCH with the complaints of redness left eye with left sided orbital swelling. She was reasonably well 15 days back, then suddenly she developed headache followed by redness, swelling with pain on left eye . She went for an eye consultation and took antibiotic eye drop and Oral antibiotic . But after taking medication she didn’t improved at all, eventually swelling and redness extended into right eye as well .She got admitted on NIKDU with orbital complaints. But she had an episode of tinge bleeding per nose and no improvement on orbital complaints . At late night she got admission on PMCH and had an another episode of severe epistaxis which was sudden onset and the amount was about 2-3 tea spoon full . On next day amount was profuse, about ½ cup full. At the same time, she developed bluish to whitish discoloration of skin over nasal area.On examination, she was ill looking, mildly anaemic, tinge bleeding per nose. Her vitais normal. Examination of nervous system reveled partial ptosis of left eye with 3,4,6 nerve palsy with mild ophthalmoplegia, movement of eyes were mildly restricted and No sign of papilledema present. Normal higher psychic function and intact other cranial nerves. Motor function and sensory function was normal and all reflexes were intact .Examination of other system was unremarkable.Histopathology report : Nasal tissue Aspergillosis ª% Sino-nasal tissue Mucormycosis. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 171-172